The effectiveness of a training program based on blended learning and gamification methods in acquiring knowledge and applying the twenty-first-century teaching skills among mathematics teachers in the basic education stage - Sawaftah, Mohammad Fa’eq; Al-Sbou, Majida Khalaf (Journal of Educational and Psychological Sciences, 2021)
The goal of the research is to show the efficacy of a training program build on the methods of blended learning and gamification in acquiring the teaching skills imposed by the 21st century among mathematics teachers who work in basic education. Therefore, the study sought to apply the semi-experimental curriculum to a group of (28) teachers who teach mathematics in Al-Nasser Modern Private Schools in Amman during the first semester of the academic year 2019/2020. To this end, a training program was built, knowledge test, and a notecard were prepared. The study concluded that there is a significant difference between the average scores of teachers in the applications of both the observational card and the cognitive test before and afterwards, due to the designed program.